2012
DOI: 10.1007/s11357-012-9451-5
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages from elders are more permissive to intracellular multiplication of Mycobacterium tuberculosis

Abstract: The elderly account for a disproportionate share of all tuberculosis cases, and the population ageing may not fully explain this phenomenon. We have performed in vitro infection experiments to investigate whether there is an immunological basis for the apparent susceptibility of elders to tuberculosis. In our infection model, Mycobacterium tuberculosis induces a higher production of interleukin (IL)-6 and reactive oxygen species in macrophages from elders than from younger adults. This response did not prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Examples include Varicella Zoster which can become active to produce shingles in older people (Levin 2012) Fig. 2 Events occurring during the ageing process, their contribution to the increase in MDSCs, and the consequences for immunity in older individuals and tuberculosis (TB) (Guerra-Laso et al 2013) which can occur in older adults who had previously had immunity to this infection.…”
Section: Infections Mdscs and Ageingmentioning
confidence: 99%
“…Examples include Varicella Zoster which can become active to produce shingles in older people (Levin 2012) Fig. 2 Events occurring during the ageing process, their contribution to the increase in MDSCs, and the consequences for immunity in older individuals and tuberculosis (TB) (Guerra-Laso et al 2013) which can occur in older adults who had previously had immunity to this infection.…”
Section: Infections Mdscs and Ageingmentioning
confidence: 99%
“…In a recent report we have taken advantage of the Design of Experiments methodology (DOE) based on factorial designs 91 92 , which we had never been able to observe with one-factor-at-a-time experiments 78 , and has been very useful for identifying factors that influence mycobacterial growth, like cytokines, age or protein tyrosine phosphorylation inhibitors. Even when we are interested in only one factor, the addition of factors like…”
Section: Statistical Data Analysismentioning
confidence: 99%
“…The trend of tuberculosis into aged individuals appears to be explained by the ageing of the population . Nevertheless, we have recently reported that there might be a cellular basis for this susceptibility because M. tuberculosis multiplies faster within macrophages from the elderly than from adults . Therefore, older individuals comprise a suitable group for analysing tuberculosis susceptibility.…”
Section: Introductionmentioning
confidence: 99%